Variations in Foliage and Soil Nutrient Composition in Acacia tortilis Plantation of Different Ages in North-western Rajasthan - Singh, G.; Singh, Bilas; Kuppusamy, V.; Bala, N. (Indian Forester, 2002)
Investigations were made on soil properties and foliage nutrient compositions under four age classes of Acacia tortilis (L) Forsk plantation to determine the nutrient buildup and the impact of Acacia tortilis plantation on soil properties. The study was carried out through simple random sampling using four stands of different ages viz 4 years (Y4) , 9 years (Y9 ) , 12 years (Y12) and 19 years (Y19). Elemental concentration of A. tortilis foliage differed significalltly (P<O.O01) with stand age except for Ca and Cu. Foliage N , P , Ca and Cu were low in young stand (Y4) and increased with increasing stand age. Mg , K , Zn , Mn and Fe showed a reverse trend that was attributed to the effect of irrigation during the first five years and increased competition for resources in older stands. Most of the soil nutrients were higher in plantation area compared to control area (Yo). Soil organic carbon (SOC) increased with increasing age of the stand , influencing the soil pH and soil nutrient availability. Soil available nitrogen N (NH4-N+NO3-N) , P04-P , Ca , Cu , Zn and Fe increase through SOC/litter accumulation. K and Zn also showed increasing trend , though the availability was less compared to Y0 area and was due to higher utilisation in actively growing young plantation. Extractable Mg decreased with age and was probably utiJised in stand development. Accumulation was greater in 0-15 cm soil layer compared to 15-30 em layer. The increased soil nutrients under A. tortilis plantation had direct impact on site improvement. Thus the study suggests that the species can be utilised in wasteland development and other afforestation programmes.